2019 IEEE 58th Conference on Decision and Control (CDC) 2019
DOI: 10.1109/cdc40024.2019.9029217
|View full text |Cite
|
Sign up to set email alerts
|

Distributed stochastic optimization with gradient tracking over strongly-connected networks

Abstract: In this paper, we study distributed stochastic optimization to minimize a sum of smooth and strongly-convex local cost functions over a network of agents, communicating over a strongly-connected graph. Assuming that each agent has access to a stochastic first-order oracle (SFO), we propose a novel distributed method, called S-AB, where each agent uses an auxiliary variable to asymptotically track the gradient of the global cost in expectation.The S-AB algorithm employs row-and column-stochastic weights simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 29 publications
1
76
0
Order By: Relevance
“…An interesting attribute of some distributed stochastic methods is that they achieve a variance reduction effect similar to mini-batching [25], [41], [43], [46], [50], [53]. However, only a small subset of methods can achieve linear convergence [25], [34], [46], [50]- [52]. In addition, none of these methods is adaptable to varying application conditions and some of them have excessive memory requirements [25], [34] or rely on data reshuffling schemes [51].…”
Section: Introductionmentioning
confidence: 99%
“…An interesting attribute of some distributed stochastic methods is that they achieve a variance reduction effect similar to mini-batching [25], [41], [43], [46], [50], [53]. However, only a small subset of methods can achieve linear convergence [25], [34], [46], [50]- [52]. In addition, none of these methods is adaptable to varying application conditions and some of them have excessive memory requirements [25], [34] or rely on data reshuffling schemes [51].…”
Section: Introductionmentioning
confidence: 99%
“…Solutions to the aggregate optimization problem (2) can be pursued by a variety of decentralized algorithms, including primal [1][2][3]8] and primal-dual [9][10][11][12][13] methods. The notion of -differential privacy as a means of quantifying the privacy loss encountered by sharing functions of private data is due to [7,14], as is the Laplace mechanism, which ensures -differential privacy by perturbing the output of the function by Laplacian noise, where the power of the perturbation is calibrated to the sensitivity of the function and the desired privacy level .…”
Section: Related Workmentioning
confidence: 99%
“…We denote • 2 and ||| • ||| as the Euclidean vector norm and the spectral (matrix) norm, respectively. Since ρ(B − B ∞ ) < 1, it can be shown that there exists a matrix norm ||| • ||| π , formally defined in [20], such that λ := ||| B − B ∞ ||| π < 1.…”
Section: Introduction and Related Workmentioning
confidence: 99%